Validation and evaluation of commercially available compounds for use as beef and pork antimicrobial interventions - Pittman, Curtis Ira, author; Belk, Keith E., advisor; Woerner, Dale R., committee member; Goodridge, Lawrence D., committee member; Kendall, Patricia A., committee member (Colorado State University. Libraries, 2011)
Studies were conducted to validate the use of various antimicrobial chemicals to be used as antimicrobial interventions of chilled subprimals and hot beef carcasses. Chemicals evaluated on surrogate Escherichia coli biotype 1 (BAA-1427, BAA-1428, BAA-1429, BAA-1430, and BAA-1431) inoculated at approximately 6.0 log CFU/cm2 on beef and pork subprimals included lactic acid (2.0, 2.5, and 5.0%), Sodium Bisulfate (2.5%), lactic acid/Sodium Bisulfate mixture (3.0 and 6.0%), BlitzTM (180 and 220 ppm), Inspexx 200TM (100 and 220 ppm), SYNTRx 3300 (pH = 1.2), citrus essential oils (3.0 and 6.0%), and deionized water. Chemicals were applied at in a custom-built spray cabinet with stainless steel slotted conveyor belt (Chad Co., Olathe KS) at two pressures (1.03 and 4.83 bar) and two rate of applications (0.23 and 6.62 lpm). After treatment bacterial counts were lower on samples treated with SYNTRx 3300, compared to other treatments. After treatment counts on samples treated with Blitz, lactic acid, sodium bisulfate, and lactic acid/sodium bisulfate mixtures were similar. Counts after treatment on samples treated with Inspexx and water were similar and higher than other chemicals due to a washing effect and not a chemical effect. Lactic acid can reduce microbial contamination on beef carcass surfaces when used as a food safety intervention, but effectiveness when applied to the surface of chilled beef subprimals is not well documented. Studies characterizing bacterial reductions from lactic acid on subprimals would be useful in validations of HACCP systems. The objective of this study was to validate initial use of lactic acid as a subprimal intervention during beef fabrication, followed by a secondary application to vacuum-packaged rework product following removal of packaging. Chilled beef subprimal sections (100 cm2) were either left uninoculated or were inoculated with 6 log CFU/cm2 of a 5-strain mixture of Escherichia coli O157:H7, a 12-strain mixture of non-O157 Shiga toxin-producing E. coli (STEC), or a 5-strain mixture of non-pathogenic (biotype I) E. coli considered surrogates for E. coli O157:H7. Uninoculated and inoculated subprimal sections received an initial or initial and second, "re-work" application of lactic acid in a custom-built spray cabinet at one of 16 different application parameters. Following the initial spray, total inoculum counts were reduced from 6.0 log CFU/cm2 to 3.6, 4.4, and 4.4 log CFU/cm2 for the E. coli surrogates, E. coli O157:H7, and non-O157 STEC inoculation groups, respectively. After the second, re-work application, total inoculum counts remaining were 2.6, 3.2, and 3.6 log CFU/cm2 for the E. coli surrogates, E. coli O157:H7, and non-O157 STEC inoculation groups, respectively. Both the initial and secondary lactic acid treatments effectively reduced counts of pathogenic and non-pathogenic strains of E. coli, as well as natural microflora, on beef subprimals. Studies characterizing bacterial reductions when chemicals are applied to beef carcass tissue would be useful in validations of HACCP systems. The objective of this study was to validate use of BoviBrom as a hot carcass intervention during beef slaughter processes. Beef cutaneous trunci muscle segments (100 cm2 of exposed surface lean) were assigned to four groups: 1) inoculated with 4 log of a 5-strain Escherichia coli O157:H7 cocktail, 2) inoculated with 4 log of a 12-strain, non-O157 shiga toxin-producing E. coli (STEC) cocktail, 3) inoculated with 4 log of a 5-strain non-pathogenic E. coli and Salmonella surrogate cocktail, and 4) not inoculated. Application of BoviBrom occurred in a custom-built spray cabinet at four temperatures (40, 80, 100, and 120°F), three pressures (15, 90, and 120 psi), and three doses (0.5, 1.0, and 1.5 ml/cm2), at a single concentration (225 ppm). At sampling time, 100 cm2 sections were homogenized for 120 seconds in 100 ml of 0.1% buffered peptone water and serially-diluted (10-fold) in 0.1% buffered peptone water. Appropriate dilutions were spread plated (0.1 ml) onto non-selective media [tryptic soy agar (TSA)] and selective media [TSA plus rifampicin (100μg/ml)] to determine total plate count (TPC) and total inoculated count (TIC), respectively. Following initial BoviBrom application, varying application parameters did not affect the after treatment counts, with the exception of pressure of application as TPC and TIC were far higher when BoviBrom was applied at 15 psi. No difference (P > 0.05) was observed between samples treated with different temperatures or doses. No difference (P > 0.05) was observed between samples enumerated immediately following treatment and samples enumerated at 24 hours post-treatment. TPC and TIC after treatment counts were lower on samples treated with BoviBrom when compared to samples treated with only water, showing a portion of the lower counts can be attributed to the chemical action of BoviBrom. These data would be beneficial to industry as part of the HACCP validation process.
Keywords: pork; intervention; STEC; beef; E. coli O157:H7